Answer:
Here we can only answer A and B.
For a given function f(x), the average rate of change in a given interval [a, b] is given by:
![r = (f(b) - f(a))/(b - a)](https://img.qammunity.org/2022/formulas/mathematics/college/mih5ey1mymdw4x4ottkycg23ttvht10ilh.png)
A) we have g(x) = 14*x + 6, and the interval [0, 5], the average rate of change is:
![r = (g(5) - g(0))/(5 - 0) = ((14*5 + 6) - (14*0 + 6))/(5) = (14*5)/(5) = 14](https://img.qammunity.org/2022/formulas/mathematics/college/mbsxkcanxq4yrqqidaowhvhtohpw3v87rr.png)
The average rate of change is 14.
B) We have g(x) = 3*(2x) - 6
we can rewrite this as:
g(x) = 3*2*x - 6 = 6x - 6
And we want to find the rate of change in the interval [0, 5]
is:
![r = (g(5) - g(0))/(5 - 0) = ((6*5 - 6) - (6*0 - 6))/(5) = 6](https://img.qammunity.org/2022/formulas/mathematics/college/o4lbogmif0ys7ppjcvyxpgf96tuyxr01qf.png)